Are markets efficient? The extreme case of corporate bankruptcy - a systematic review - Coelho, Luis (Cranfield University, 2005)
Fama (1970) presents the classical definition of an efficient market: in such a market, prices always reflect all available information. Recently, behavioural finance has emerged as an alternative theoretical framework to the traditional paradigm. This new approach is based on the idea that not all investors are rational and that rational investors face limits to arbitrage. The market's reaction to corporate bankruptcy announcements is a privileged context within which to explore the conflicting predictions of these two competing theoretical frameworks. In fact, existing research does not provide clear guidance on this issue. Some studies suggest that the market is efficient in the event of corporate failure (e.g. Clark and Weinstein, 1983; Morse and Shaw, 1988; Elayan and Maris, 1991) while others conclude that the market is highly inefficient when dealing with extreme bad news (e.g. Katz et al, 1985; Eberhart et al, 1999; Indro et al, 1999). This study resorts to the systematic literature review methodology to organize a survey on the existing literature that analyses the market's reaction to corporate bankruptcy announcements. The purpose of the review is to identify suitable research gaps that can be explored at a PhD level. A brief overview of the thematic under analysis is presented in the first part of the study. Subsequently, a detailed analysis of the systematic literature review methodology is provided, including both the search strategy employed and the different selection criteria used. The last part presents the results. These suggest that the area under analysis has received considerable attention from the finance academic community but some interesting research questions still remain unsettled, providing the context for future research in the field.